GEDUNG GEREJA SEBAGAI TEMPAT KAUM BERIMAN BERIBADAT KEPADA ALLAH DALAM ROH DAN KEBENARAN - Rahawarin, B.A (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2012)
This paper presents a biblical-theological significance of the Church building. The central idea is to maintain a Chuch building as a home to the faithful in order to celebrate the liturgy. One role of a Church building is to present an image of the Church as the Temple of the human and natural levels. This suggests that the mystery of the Church as the People of God becomes visivle within the limits of space and time. In its function as a place of worship of the people, thye Chuch gains its true identity